Will skyscrapers save the planet? - Rainald Borck (European Regional Science Association (ERSA), 2014)
This paper studies the effectiveness of building height limits as a policy to limit greenhouse gas (GHG) emissions. It shows that building height limits lead to urban sprawl and higher emissions from commuting. On the other hand, aggregate housing consumption may decrease which reduces emissions from residential energy use. The paper uses numerical simulation to show that total GHG emissions may be lower under building height restrictions. It also studies the effect of endogenous transport technology and the urban heat island effect.
Keywords: Q5; R1; 330; greenhouse gas emissions; city structure; building height limits